Partial Heart Transplantation Promotes Organ Stewardship: Domino Hearts and Split Roots - Berk Aykut, MD; Douglas M. Overbey, MD, MPH; Cathlyn K. Medina, BA; Tariq M. Omer, MS; T. Konrad Rajab, MD; Smith M. Ngeve, BA; Ziv Beckerman, MD; Joseph W. Turek, MD, PhD (Annals of Thoracic Surgery Short Reports)
Background: Partial heart transplantation (PHT) has emerged as a pioneering approach for treating infants with irreparable heart valve dysfunction. However, the scarcity of suitable donors presents a significant bottleneck to its widespread application. This study introduces and evaluates the novel use of domino and split-root procedures within PHT. Methods: We describe 6 pediatric cardiac patients who underwent either domino or split-root PHT at our institution. Results: From May to August 2023, our team successfully executed 3 domino and 3 split-root PHTs, including 1 procedure that involved interinstitutional collaboration. These cases highlight the procedural feasibility and the potential for broader application. Conclusions: The implementation of PHT represents a significant advance in pediatric heart care. Domino and split-root techniques within the PHT framework have the potential to substantially increase both donor availability and recipient capacity. These strategies usher in a new era of organ stewardship through addressing the challenge of donor organ shortage.